Curcumin Suppressed Activation of Dendritic Cells via JAK/STAT/SOCS Signal in Mice with Experimental Colitis - Hai-mei Zhao; Rong Xu; Xiao-ying Huang; Shao-min Cheng; Min-fang Huang; Hai-yang Yue; Xin Wang; Yong Zou; Ai-ping Lu; Duanyong Liu (Frontiers Media S.A., 2016)
Dendritic cells (DCs) play a pivotal role as initiators in the pathogenesis of inflammatory bowel disease and are regulated by the JAK/STAT/SOCS signaling pathway. As a potent anti-inflammatory compound, curcumin represents a viable treatment alternative or adjunctive therapy in the management of chronic inflammatory bowel disease (IBD). The mechanism of curcumin treated IBD on DCs is not completely understood. In the present study, we explored the mechanism of curcumin treated experimental colitis by observing activation of DCs via JAK/STAT/SOCS signaling pathway in colitis mice. Experimental colitis was induced by 2, 4, 6-trinitrobenzene sulfonic acid (TNBS). After 7 days treatment with curcumin, its therapeutic effect was verified by decreased colonic weight, histological scores and remitting pathological injury. Meanwhile, the levels of major histocompatibility complex class II (MHC-II) and DC costimulatory molecules (CD83, CD28, B7-DC, CD40, CD40 L and TLR2) were inhibited and followed the up-regulated levels of IL-4, IL-10 and IFN-γ, and down-regulated GM-CSF, IL-12p70, IL-15, IL-23 and TGF-β1. A key finding was that the phosphorylation of the 3 members (JAK2, STAT3 and STAT6) of the JAK/STAT/SOCS signaling pathway was inhibited, and the 3 downstream proteins (SOCS1, SOCS and PIAS3) from this pathway were highly expressed. In conclusion, curcumin suppressed the activation of DCs by modulating the JAK/STAT/SOCS signaling pathway to restore immunologic balance to effectively treat experimental colitis.